Structuring an Elementary-School Science Program. - Fish, Alphoretta S. (Elementary School Journal, 1963)
The article focuses on science teaching programs that are conducted in elementary schools. Science is the study of relationships and the derivation of fundamental principles. Science curriculum should help students in learning about the environment. The technique of relating the familiar to the unfamiliar, helps a child in discovering new scientific concepts, and understanding the learning process.